The Twilight of Sovereignty - Wriston, Walter B. (Tufts Archival Research Center, 2007)
This document was created from the article, "The Twilight of Sovereignty" by Walter B. Wriston for the Summer 1993 edition of the "Fletcher Forum of World Affairs." The original article is located in MS134.003.028.00002.